Calcification of the filamentous cyanobacterium Blennothrix ganeshii in calcareous tropical streams of central Mexico region - Beltrán-Magos, Yenny; Carmona, Javier; Vilaclara, Gloria; Bojorge-García, Miriam (HIDROBIOLÓGICA, 2017)
Geochemical, mineralogical and microbiological data from four freshwater streams in central region of Mexico indicate the importance of Blennothrix ganeshii mats (Cyanobacteria, Oscillatoriales) in promoting the formation of calcium carbonate crystals. The streams were characterized by alkaline waters and relative physicochemical stability during three seasons (cold dry, warm dry and warm rainy). Calcification took the form of a thick, dense layer of calcium carbonate crystals surrounding the extracellular polymeric substances produced by B. ganeshii filaments, giving an appearance of micritic tubes (structures formed by crystallization in the spaces between filaments) along the sheath surfaces. The precipitate was analyzed using X-ray diffraction and energy dispersal X-ray spectrometry, and the calcite crystal habit was determined. The photosynthetic activity of cyanobacterial growth and the presence of abundant extracellular polymeric substances and epiphytic species promote the absorption of ions and mineral nucleation on the surface of the sediment and contribute to the formation of travertine in tropical regions.